Optimization of enzymatic synthesis of 3-O-β-D-glucopyranoside betulinic acid by Novozyme-435 - Abdu, Hamisu; Ahmad @ Amat, Faujan; Basri, Mahiran; Ismail, Intan Safinar; Abdul Rahman, Mohd Basyaruddin (A & V Publications, 2014)
The enzymatic synthesis of 3-O-β-D-glucopyranoside betulinic acid using Novozyme-435 as a catalyst was studied. The effects of various parameters such as reaction temperature, reaction time and amount of enzymes were investigated. The optimum reaction conditions for the synthesis of 3-O-β-D-glucopyranoside betulinic acid was obtained using 30.67 h, 54.30°C and 180 mg of enzymes using betulinic acid (0.05 mmol) and glucose (0. 1 mmol) respectively. The actual percentage yield under these conditions was 88.69 % and the predicted value was 89.05 %.